Hadhanah Dispute Settlement Process Due to Avoid Wife According to Wahbah Al-Zuhaili and Its Relevance to Islamic Law in Indonesia - Karma, Adi (IAIN Parepare, 2022)
In Islam, marriage between a Muslim man and a non-Muslim woman is absolutely prohibited. If in a marriage there is a divorce because the wife is out of her religious belief (apostasy), then there is a dispute over the authority of whether the wife can carry out maintenance in the form of care for her child or not. The majority of mazhab scholars allow infidel wives to perform hadhanah on the grounds that mothers have more love for their children. However, Wahbah Az-Zuhaili in his book Fiqhul Islami waadilatuhu, argues that the right to hadhanah is not stipulated for an apostate wife. Based on the explanation above, the main problem raised in this thesis is how the concept of hadhanah according to Wahbah Az-Zuhaili,